Composition, Quoracy and Cost of Specialist Skin Cancer Multidisciplinary Team Meetings in the United Kingdom. Issue 12 (December 2021) - Ali, Stephen R.; Dobbs, Thomas D.; Hutchings, Hayley A.; Whitaker, Iain S.
Summary: Background: Multidisciplinary team (MDT) meetings are an integral component of skin cancer service provision, enabling the implementation of evidence-based decisions and standardised patient outcomes. Objectives: We sought to evaluate the composition, quoracy and cost of Specialist Skin Cancer Multidisciplinary Teams (SSMDTs) in the United Kingdom (UK) to establish the functionality and financial impact of these meetings. Methods: Cross-sectional design with a national freedom of information request made to 65 NHS trusts in the UK hosting an SSMDT. Detailed information with regard to attendance frequency and core membership from attendance registers was requested. Quoracy was measured against the 2006 National Institute for Health and Care Excellence Cancer Services standard 'Improving outcomes for people with skin tumours including melanoma'. We costed the SSMDT utilising the running time, core membership salaries derived from national pay scales and overhead values provided by trusts. Results: Out of 58 respondents (89% response rate), only 15 SSMDTs (26%) were quorate by membership. Forty SSMDTs (69%) were quorate by meeting frequency. The main reasons for membership noncompliance was lack of clinical oncology presence. There was a large variation in the cost per patient (µ = £132.68, range: £31.67-£313.10). There was no geographical variation in quoracy or cost between England, Wales, Scotland and Northern Ireland.